“My pharmacist”: Creating and maintaining relationship between physicians and pharmacists in primary care settings - Mercer, Kathryn; Neiterman, Elena; Guirguis, Lisa; Burns, Catherine; Grindrod, Kelly (Elsevier, 2020)
Background Pharmacists and physicians are being increasingly encouraged to adopt a collaborative approach to patient care, and delivery of health services. Strong collaboration between pharmacists and physicians is known to improve patient safety, however pharmacists have expressed difficulty in developing interprofessional working relationships. There is not a significant body of knowledge around how relationships influence how and when pharmacists and physicians communicate about patient care. Objectives This paper examines how pharmacists and primary care physicians communicate with each other, specifically when they have or do not have an established relationship. Methods Thematic analysis of data from semi-structured interviews with nine primary care physicians and 25 pharmacists, we examined how pharmacists and physicians talk about their roles and responsibilities in primary care and how they build relationships with each other. Results We found that both groups of professionals communicated with each other in relation to the perceived scope of their practice and roles. Three emerging themes emerged in the data focusing on (1) the different ways physicians communicate with pharmacists; (2) insights into barriers discussed by pharmacists; and (3) how relationships shape collaboration and interactions. Pharmacists were also responsible for initiating the relationship as they relied on it more than the physicians. The presence or absence of a personal connection dramatically impacts how comfortable healthcare professionals are with collaboration around care. Conclusion The findings support and extend the existing literature on pharmacist-physician collaboration, as it relates to trust, relationship, and role. The importance of strong communication is noted, as is the necessity of improving ways to build relationships to ensure strong interprofessional collaboration.
The final publication is available at Elsevier via https://doi.org/10.1016/j.sapharm.2019.03.144. © 2019. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: collaboration; communication; pharmacy; patient care